Problematika Hak Waris Atas Tanah Warisan Bagi Ahli Waris Beda Agama - Iwan Permadi (Fakultas Hukum Universitas Islam Malang, 2023)
Due to the absence of an adequate legal umbrella and the strong religious beliefs and adherence of the Indonesian people, the issue of inheritance rights to land for heirs of different religions is far from being resolved without conflict and dispute. The research method used is normative juridical with the method of statutory approach, and conceptual approach. The results of the study show that the fulfilment of rights to inheritance land due to religious differences can be done by mandatory wills by court decisions and grants by the testator while still alive. There is jurisprudence that can be used as a basis for consideration by judges in deciding this case. The transfer of land rights must be registered with the Badan Pertanahan Nasional accompanied by supporting documents and a court decision after it has permanent legal force.